Sociolinguistic Factors Influencing the Acquisition of English Vocabulary in Multilingual Contexts: Insights from Selected Secondary School Teachers in Dodoma, Tanzania - Godson Robert Mtallo; Gerald Kimambo (Journal of Modern Research in English Language Studies)
The study aimed to investigate the influence of sociolinguistic factors on the acquisition of English vocabulary in multilingual contexts. It employed a case study design in Dodoma City and Chamwino District Councils in Dodoma Region, Tanzania. Purposive sampling was used to select eight English language teachers, all of them having at least five years’ teaching experience. Selected teachers participated in semi-structured interviews to gather qualitative data, which underwent content analysis through Nvivo 12. The findings of the study indicate that sociolinguistic factors, such as the learners' first language, the level at which they started learning English, the education level of their parents, and opportunities to interact with English-speaking children, positively impact the acquisition of English vocabulary. Attention should be paid to the social and cultural backgrounds of learners when elucidating the process of acquiring vocabulary in a second/foreign language within multilingual environments. Based on these findings, teachers and policymakers should consider the sociolinguistic backgrounds of learners when designing language teaching programmes. They should provide support for learners who may start learning English at a later age to improve English in multilingual contexts.